2-Amino-4,6-dimethylpyridinium benzoate - Mohd Razip, Asaruddin; Habibah, A Wahab; Nornisah, Mohamed; Fun, Hoong-Kun (IUCR, 2010)
In the title compound, C7H11N2 +·C7H5O2 −, the 2-amino-4,6-dimethylpyridinium cation and the benzoate anion are linked by two N—H⋯O hydrogen bonds, forming an R 2 2(8) ring motif. The H atoms in both the methyl groups are rotationally disordered, with fixed site occupancies of 0.50. In the crystal structure, the molecules are stabilized by intermolecular N—H⋯O hydrogen bonds. A π–π interaction, with a centroid–centroid distance of 3.661 (2) Å, is also observed.